DESIGN ALAT REKAYASA ARUS PEMBANGKIT LISTRIK TENAGA ARUS SUNGAI LAGAN DI DESA LAGAN TENGAN KABUPATEN TANJUNG JABUNG TIMUR - Myson Myson (Universitas Batanghari Jambi, 2014)
Need of the Indonesia people kept rising, while supply energy electricity the goverment is very limited. As we know that country has various sorts of the type renewebel energy. For those it shall meet the needs of innovations in energy. River lagan in the catch of the middle lagan village have smoll flow but with innovation engineering, river flow can be to meet the need of the village.Key word : River flow , renewebel energy, water turbin